2015
DOI: 10.1161/circulationaha.114.014704
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and Clinical Significance of Poststent Optical Coherence Tomography Findings

Abstract: The aims of this study were (1) to evaluate the incidence of poststent findings detected by OCT from multicenter experience, (2) to correlate these poststent findings with 1-year device-oriented clinical end points (DoCEs), including cardiac death, target vessel-related myocardial infarction, target Background-Optical coherence tomography (OCT) was recently introduced to optimize percutaneous coronary intervention. However, the exact incidence and significance of poststent OCT findings are unknown. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
153
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(182 citation statements)
references
References 35 publications
9
153
2
5
Order By: Relevance
“…Severe diameter stenosis and subsequent differences between the luminal diameter of the most stenotic segment and that of the reference vessel also increase the frequency of ASM 19. Heavily calcified lesions are prone to ASM, despite high‐pressure balloon dilation or rotational atherectomy 22, 23. In our study, there was a higher prevalence of ASM in the right coronary artery.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Severe diameter stenosis and subsequent differences between the luminal diameter of the most stenotic segment and that of the reference vessel also increase the frequency of ASM 19. Heavily calcified lesions are prone to ASM, despite high‐pressure balloon dilation or rotational atherectomy 22, 23. In our study, there was a higher prevalence of ASM in the right coronary artery.…”
Section: Discussionsupporting
confidence: 47%
“…At 2‐year follow‐up combining BMS and paclitaxel‐eluting stents, there were no significant differences in MACE rates for patients with ASM (17.1%) versus no ASM. In the recent OCT studies of Prati et al21 (49.3% of ASM with stent to adjacent vessel distance >200 μm in 984 lesions of 832 patients) and Soeda et al22 (39.1% of ASM in 900 lesions of 786 patients), OCT‐detected ASM was not a predictor of 1‐year MACE.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In post-PCI OCT, suboptimal stent deployment, including distal stent edge dissection, which was most frequent in our 3 rd tertile group, is associated with a higher risk of adverse events during follow up 25 . In recent study, Soeda et al observed that irregular protrusion was an independent predictor of device-oriented clinical endpoints at 1-year 10 . Combined with our results, the association of high SS and adverse cardiac events may be explained.…”
Section: Similar Findings Have Been Reported By Brugaletta Et Al Andmentioning
confidence: 98%
“…OCT evaluation before PCI included lipid rich plaque, lipid arc, lipid index, fibrous cap thickness (FCT), thincap fibroatheroma (TCFA), calcium deposits, and microchannels [7][8][9] . Post-stent OCT evaluation included mallaposition, stent edge dissection, intra-stent dissection, and irregular protrusion [10][11][12] . OCT images were analyzed by 2 investigators who were blinded to subject information, including SS.…”
Section: Page 3 Of 23mentioning
confidence: 99%